2015
DOI: 10.1097/md.0000000000000841
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Papillary Thyroid Microcarcinomas Using Sonographic Features in Malignant Papillary Thyroid Cancer

Abstract: The diagnosis of malignant thyroid nodules is still a clinical challenge. This study aimed to determine the ultrasonographic characteristics of papillary thyroid carcinoma.The ultrasonographic and pathological data of 2453 thyroid nodules in a cohort of 1895 Chinese patients who underwent thyroidectomy from January 2010 to December 2012 were retrospectively reviewed.Anteroposterior and transversal (AP/TR) diameters ≥1, solid structure, infiltrative margins, hypoechoic appearance, and microcalcifications were m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 19 publications
1
10
0
1
Order By: Relevance
“…Although ultrasonography is very sensitive for the identification of cervical nodal compartments metastases, the specificity is low and the prescribed regions are limited, which impedes its use in the identification of distant metastases. [ 26 , 27 ] Meanwhile, controversies on the utility of Dx-WBS in guiding 131 I therapeutic decision making still exist, and predictors on the outcome of 131 I therapy of DTC are unavailable at present. [ 2 ]…”
Section: Discussionmentioning
confidence: 99%
“…Although ultrasonography is very sensitive for the identification of cervical nodal compartments metastases, the specificity is low and the prescribed regions are limited, which impedes its use in the identification of distant metastases. [ 26 , 27 ] Meanwhile, controversies on the utility of Dx-WBS in guiding 131 I therapeutic decision making still exist, and predictors on the outcome of 131 I therapy of DTC are unavailable at present. [ 2 ]…”
Section: Discussionmentioning
confidence: 99%
“…Currently, thyroid nodules are primarily evaluated by ultrasonography and fine-needle aspiration biopsy. For suspected thyroid nodules, though cytology is an effective diagnostic method, invasiveness limited the clinical application [ 7 ]. Ultrasonography is a convenient, cost effective, highly sensitive and noninvasive preoperative diagnostic method, and it has been the preferred screening method [ 8 ].…”
Section: Discussionmentioning
confidence: 99%
“…Similar to our results, Moon et al reported that fewer malignant nodules ≤10 mm had microcalcification than larger nodules, and the diagnostic value of microcalcification was greater for large nodules than for small nodules [ 9 ]. In some nodules ≤10 mm, it might be difficult to differentiate microcalcifications from colloid crystals, and this may be an explanation for why calcification was more common in PTMC >5 mm [ 7 ].…”
Section: Discussionmentioning
confidence: 99%
“…For a person to be detected, there must exist a nodule greater than 3 mm, which represents a conservative limit of sonographic technology [1921]. The model input parameters (prior to calibration) are shown in Table 1.…”
Section: Methodsmentioning
confidence: 99%